Case report: Lamin A/C gene mutation in patient with drug-induced type 1 Brugada syndrome at high arrhythmic risk - Russo, Vincenzo; Papaccioli, Giovanni; Maddaloni, Valeria; Caputo, Adriano; Pepe, Nicola; Rago, Anna; Maiorino, Michele; Golino, Paolo; Nigro, Gerardo (Frontiers in Cardiovascular Medicine, 2023)
We report the case of drug-induced type 1 Brugada syndrome at high arrhythmic risk associated with Lamin A/C gene mutation.